Gender Equality in Islam (Classical and Contemporary Mufassir Perspectives) - Subhan Abdullah Acim (Budapest International Research and Critics Institute-Journal (BIRCI-Journal), 2022)
Gender is the differentiation of roles, functions, and responsibilities between women and men resulting from socio-cultural construction and can change according to the times. Gender can also be understood as social sex. The research method used is qualitative research with a literature study approach. Data collection techniques are sourced from documentation of books, articles, etc. This is then analyzed to conclude from various written documents by systematically and objectively identifying a message or data in its context. This article aims to find out how Islam's view of gender equality is extracted from the opinions of commentators in interpreting the Qur'an, especially in Surah an-Nisa verses 1 and 34. The study results show that Islam is not a misogynistic religion, but in this gender issue, Islam has regulated several different rights and obligations for men and women by giving specificity as a gift from Allah SWT. Men and women are like heads and limbs. So, as an inseparable unit, we must cooperate and respect each other, and there is no need to feel superior and the other inferior.